No relationship between running related injuries and kinetic variables. Issue 4 (27th March 2011) - Bredeweg, S; Buist, I
Abstract : Background: Although the benefits of running are well known, 19–79% of the runners get injured every year. Many risk factors are associated with the aetiology of running-related injuries, but still there is no consensus on the exact cause of running injuries. Kinetic variables, such as impact peak force, active peak force and the impact loading rate are scarcely studied in novice runners. Studies on the aetiology of stress fractures of the tibia showed conflicting results between kinetic factors and the development of stress fractures of the tibia. Objective: To examine the effects of running kinetics on the incidence of running related injuries in novice recreational runners. Design: Prospective cohort study. Kinetic variables were acquired from an instrumented treadmill with three force measuring transducers. Female participants ran at 2.2 m/s and 2.5 m/s and male participants at 2.5 m/s and 2.78 m/s. At each velocity the vertical ground reaction forces were measured, from which the kinetic variables were calculated. Setting: Novice recreational runners. Participants: 98 male and 100 novice female runners, mean age 39.8 years and a body mass index of 25.4 were included in the study and were followed for 9 weeks during the training program. Intervention: The occurrence of a running related injury in a 9 week training program. Main outcome measurement: A running related injury. Results: The incidence of running related injuries was 20.4%. Injured runners showed higher values on the active force peak (2.24 BW vs 2.11 BW) and higher values on the loading rate (92.5 BW/s vs 86.4 BW/s) compared to the non-injured runners. These differences however were not significant. Conclusion: This study showed no significant differences in kinetic variables between injured and non-injured novice recreational runners during a 9 week training program.